Diaphragm and Lung Ultrasound Indices in Prediction of Outcome of Weaning from Mechanical Ventilation in Pediatric Intensive Care Unit - Abdel Rahman, Dalia A. (Indian J Pediatr, 2020)
OBJECTIVE: To predict the added value of diaphragmatic and lung ultrasound indices (US) in anticipation of the outcome of mechanical ventilation of pediatric patients in the intensive care unit. METHODS: This prospective study was conducted in Zagazig University, Pediatric Hospitals, PICU; Egypt. One hundred six mechanically ventilated children aged between 1 mo to 170 mo were included in the study. All patients were candidates for weaning and have been given a chance for spontaneous breathing trial (SBT), during which diaphragmatic and lung US was performed for them. The diaphragm thickening fraction (DTF), the diaphragmatic excursion and the lung US score (LUS), that included 4 US aeration forms, were assessed. RESULTS: There were statistically significant differences between patients with failed weaning and those with successful weaning regarding DTF, diaphragmatic excursion and LUS (p < 0.001). The best cut-off value of DTF, diaphragmatic excursion, and LUS for predicting weaning failure was ≥23.175%, ≥ 6.2 mm, and ≥ 12 with an AUC (area under curve) of 0.932, 0.876, and 0.934, respectively. CONCLUSIONS: Diaphragmatic and lung US add a quick, accurate and non-invasive indices to the weaning readiness parameters compared to the other standard parameters alone. So, it is recommended to be added to the predictive parameters of weaning outcome.